2009
DOI: 10.1016/j.jcv.2009.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Natural human infections with Vaccinia virus during bovine vaccinia outbreaks

Abstract: This study confirms the high clinical frequency of human VACV infection, even among vaccinated individuals. The infection was related to detection of IgG- or IgM-specific antibodies that correlates in most of the cases with positive PRNT. The DNAemia suggests viremia during VACV natural infections. Our data indicate that patients vaccinated against smallpox may no longer be protected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
101
2
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(121 citation statements)
references
References 28 publications
5
101
2
13
Order By: Relevance
“…First, remaining within the orthopoxviruses, reports of other zoonoses such as cowpox and buffalopox have also risen in the aftermath of smallpox eradication [59][60][61]. The data are less systematic, so quantitative comparisons are challenging, but these patterns are broadly consistent with competitive release arising from the decline of cross-immunity from smallpox and its vaccine.…”
Section: Application To Other Pathogensmentioning
confidence: 99%
“…First, remaining within the orthopoxviruses, reports of other zoonoses such as cowpox and buffalopox have also risen in the aftermath of smallpox eradication [59][60][61]. The data are less systematic, so quantitative comparisons are challenging, but these patterns are broadly consistent with competitive release arising from the decline of cross-immunity from smallpox and its vaccine.…”
Section: Application To Other Pathogensmentioning
confidence: 99%
“…However, VACV infection is fairly common in Brazil, and several outbreaks of cattle and human infections have been reported in the last decades. 5,8,25 The current report contributes to the recognition and diagnosis of vesicular diseases in cattle in Brazil. …”
mentioning
confidence: 92%
“…They reported that these two VACV-based vaccination platforms induced highly functional CD8 ϩ T cells that displayed significant levels of degranulation and the coexpression of several cytokines and the chemokine MIP1␤. However, since the last reported case of smallpox occurred several decades ago, and VACV is not a natural human pathogen (although humans can be incidental hosts [49]), it could not be determined whether the functional profile of T cells induced by VACV is similar to that of smallpoxspecific T cells in the context of a truly natural infection. Therefore, in the present study, we used the mouse model of smallpox to compare the functional capacities of CD8 ϩ and CD4 ϩ T cells that arise following natural infection (ECTV) and nonnatural infection (VACV) of mousepox-resistant C57BL/6 mice.…”
mentioning
confidence: 99%